Міжкультурна комунікація в контексті спілкування в родині (польською мовою) - Корнацька-Сквора, Ельжбета (Studies in Comparative Education, 2013)
У статті розкрито умови міжкультурної комунікації. Системна засада циркулярності, спричинена взаємовпливом членів родини, визначає важливість міжкультурної комунікації як для її ініціатора, так і для інших учасників. Згідно з системною концепцією, члени родини, перебуваючи у процесі інтеракції, виходять на новий творчий рівень, який не є сумою якостей членів родини. Статтю присвячено аналізу якостей окремих членів родини в контексті родинної системи, до якої вони належать. Дослідницька концепція, яка лягла в основу статті, базується на системній теорії. Зроблено припущення, що характер міжкультурної комунікації залежить від походження родини. Статья посвящена условиям межкультурной коммуникации. Системный фактор циркулярности, вызванный взаимовлиянием членов семьи, определяет важность межкультурной коммуникации как для ее инициатора, так и для участников. Согласно с системной концепцией, члены семьи в процессе интеракции выходят на новый творческий уровень, который является не просто суммой качеств членов семьи. Поэтому статья посвящена анализу качеств отдельных членов семьи в контексте семейной системы, к которой они принадлежат. Исследовательская концепция, легшая в основу статьи, выходит из системной теории. Сделано предположение, что характер межкультурной коммуникации зависит от происхождения семьи. The author seeks to answer the question, what are the determinants of intercultural communication. Systemic circular rule, which defines mutual impact of family members on one another, points out that the «link» which reacted is equally important to the one who started the influence first. According to the systemic concept, family members under mutual interactions create new quality and they not only constitute the community composed of the sum of its individual members’ qualities. Thus, it is justified to analyze qualities of individual family members in a view of qualities of family systems in which they live. The following research concept, which considers the systemic theory, is based on assumption that intercultural communication depends on the characteristic of the family-of-origin.